Identification of circular RNA Hsa_circ_0001879 and Hsa_circ_0004104 as novel biomarkers for coronary artery disease. (July 2019) - Wang, Laiyuan; Shen, Chong; Wang, Yanyu; Zou, Tianyu; Zhu, Huijuan; Lu, Xiaomei; Li, Lin; Yang, Bin; Chen, Jichun; Chen, Shufeng; Lu, Xiangfeng; Gu, Dongfeng
Abstract: Background and aims: The role of circular RNAs (circRNAs) in coronary artery disease (CAD) remains elusive. The aim of the present study was to profile circRNAs expression in CAD patients and assess diagnostics biomarkers for CAD. Methods: The circRNA profiles of 24 CAD patients and 7 controls were assessed by microarray. The expression levels of candidate circRNAs were further verified by qRT-PCR in large cohorts. Logistic regression analysis and receiver operating characteristic were conducted to assess the diagnostic value. Gain-of-function approach was used to determine the functional significance of validated circRNA in THP-1-derived macrophages. Results: A total of 624 circRNAs and 171 circRNAs were significantly upregulated and downregulated, respectively, in CAD patients relative to controls. Hsa_circ_0001879 and hsa_circ_0004104 were validated to be significantly upregulated in large cohorts. The receiver operating characteristics analysis of hsa_circ_0001879 and hsa_circ_0004104 in CAD patients and controls showed that the area under curve was 0.703 (95% confidence interval: 0.656–0.750; p < 0.001) and 0.700 (95% confidence interval: 0.646–0.755; p < 0.001), respectively. The combination of hsa_circ_0001879 and hsa_circ_0004104, together with CAD risk factors, had the better performance to discriminate CAD patients from healthy controls. Overexpression of hsa_circ_0004104 resulted in dysregulation of atherosclerosis-related genes in THP-1-derived macrophages. Conclusions: We offered a transcriptome-wide overview of aberrantly expressed circRNAs in CAD patients and identified two novel circRNA biomarkers to diagnose CAD. Upregulation of hsa_circ_0004104 might contribute to the pathogenesis of CAD. Graphical abstract: Image 1 Highlights: We offered a transcriptome-wide overview of aberrantly expressed circRNAs in CAD patients. hsa_circ_0001879 and hsa_circ_0004104 were identified as novel circRNA biomarkers for diagnosing CAD. Hsa_circ_0004104 might contribute to the pathogenesis of atherosclerosis and CAD by regulating atherosclerosis related genes expression.